INDOMARET MILIK SIAPA? IMPLEMENTASI DAN PEMINGGIRAN PEDAGANG KECIL DALAM PRAKTEK PEMBERIAN IZIN MENDIRIKAN TOKO MODERN DI MEULABOH - Fatwa Wati; Mursyidin Mursyidin; Vellayati Hajad (Universitas Teuku Umar, 2019)
Implementation of the Republic of Indonesia's Minister of Trade Regulation regarding the presence of modern shops such as Indomaret in Meulaboh City, West Aceh Regency, which has an impact on the large number of Indomarets and disrupts the existence of traditional shops owned by local communities. This study used a qualitative method through a case study approach with key informants as Head of Trade at the Trade Office, Head of Services and Licensing Staff of the One-Stop Integrated Investment and Services Office (DPMPTSP), Secretary of the West Aceh Traders Association, Modern Shop Employees ( Indomaret), Traditional Traders / Grocer and Community Traders. The results of this study indicate that the implementation of the Permendagri issuance, especially related to structuring guidelines and fostering of traditional markets, shopping centers and modern shops carried out by the Regional Government of West Aceh Regency has not been fully effective, it is due to the absence of derivative policies governing further related the establishment of modern markets such as Indomaret, and in the implementation there is also communication and non-coordination between the two parties implementing the policy. Aside from having positive impacts such as increasing local revenue tax, Indomaret's presence also has a negative impact because it increasingly marginalizes and even kills merchant businesses in traditional shops due to shifts in consumer habits, distance or adjacent positions between modern and traditional stores.